Identification and characterization of design fires and particle emissions to be used in performance‐based fire design of nuclear facilities. (12th July 2020) - Perović, Darko; Van Hees, Patrick; Madsen, Dan; Malmborg, Vilhelm; Gren, Louise; Pagels, Joakim; Rios, Oriol; La Mendola, Saverio
Summary: CERN operates one of the most complex particle accelerator facilities in the world. Several different hazards, including fires, are present and need to be investigated and reduced to a tolerable level. Toward this goal, CERN aims at developing a catalog containing detailed fire dynamics descriptions of combustible items present in its facilities. This paper contributes to this catalog in two ways. First, through the development of a design fire calculator for electrical cabinets that allows the determination of potential design fire curves for any number of electrical cabinets/racks. The second contribution was to experimentally characterize the smoke production rates and smoke particle properties of the most common cables and insulating oils used at CERN by coupling a fast particle mobility analyzer to a cone calorimeter. The two particle size modes (accumulation and nucleation mode) could be linked to the fire properties and heat release rate. Accumulation mode particles ( 200 nm) were associated with high heat release rates and high soot emissions from the flame. This study identifies a necessity to consider ultrafine particle emissions with low mass emissions but high number emissions in relation to risk assessments pertaining to nuclear facilities and dispersion of radioactive aerosols to the surrounding environment.